Co-Delivery of p53 Restored and E7 Targeted Nucleic Acids by Poly (Beta-Amino Ester) Complex Nanoparticles for the Treatment of HPV Related Cervical Lesions - Xiong, Jinfeng; Li, Guannan; Mei, Xinyu; Ding, Jiahui; Shen, Hui; Zhu, Da; Wang, Hui (Frontiers in Pharmacology, 2022)
The p53 gene has the highest mutation frequency in tumors, and its inactivation can lead to malignant transformation, such as cell cycle arrest and apoptotic inhibition. Persistent high-risk human papillomavirus (HR-HPV) infection is the leading cause of cervical cancer. P53 was inactivated by HPV oncoprotein E6, promoting abnormal cell proliferation and carcinogenesis. To study the treatment of CIN and cervical cancer by restoring p53 expression and inactivating HPV oncoprotein, and to verify the effectiveness of nano drugs based on nucleic acid delivery in cancer treatment, we developed poly (beta-amino ester)537, to form biocompatible and degradable nanoparticles with plasmids (expressing p53 and targeting E7). In vitro and in vivo experiments show that nanoparticles have low toxicity and high transfection efficiency. Nanoparticles inhibited the growth of xenograft tumors and successfully reversed HPV transgenic mice’s cervical intraepithelial neoplasia. Our work suggests that the restoration of p53 expression and the inactivation of HPV16 E7 are essential for blocking the development of cervical cancer. This study provides new insights into the precise treatment of HPV-related cervical lesions.